An Examination of Written Work and Performance Task in General Mathematics and Precalculus of Filipino STEM Learners - Cabuquin, Jomar Cobacha (FKIP Universitas Lampung, 2023)
An Examination of Written Work and Performance Task in General Mathematics and Precalculus of Filipino STEM Learners. Objectives: This study examined the correlation between written work (WW) and performance task (PT) scores in general mathematics and precalculus of Filipino STEM learners at one public senior high school in the provincial capital of Leyte, Philippines, and compared the WW and PT scores of male and female learners. Methods: The quantitative approach using correlational and comparative designs was used to analyze the data obtained from the WW and PT scores of the 119 STEM learners (58 males and 61 females). Findings: Findings revealed a moderately positive and highly significant correlation between WW and PT scores of STEM learners. The difference in the WW and PT scores between male and female groups likewise displayed statistical significance, with the female group performing higher in WW and PT than their male counterparts. Conclusion: The development of state-of-the-art teaching strategies and practices can be utilized as input geared towards improving mathematics teaching and Filipino STEM learners' mathematics performance. Keywords: filipino stem learners, general mathematics, performance tasks, precalculus, written work.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202317